2019
DOI: 10.1002/sscp.201900031
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new solvent‐assisted dispersive solid‐phase extraction followed by ion mobility spectrometry for trace determination of organophosphorus pesticides in environmental water samples

Abstract: In this research, an effective sample preparation method called solvent‐assisted dispersive solid‐phase extraction followed by corona discharge ion mobility spectrometry was proposed for the trace determination of organophosphorus pesticides in environmental water samples. In this method, to maximize the interaction surface between target analytes and sorbent, the sorbent was dispersed into the aqueous sample. In this technique, the sorbent was dispersed at very low levels using a solution of sorbent and dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The results indicated that benzil outperformed the others (Figure 2A), which could be attributed to some interactions, such as π-π, hydrophobic, and semi-H-bond interactions between benzil and the targeted analytes. Unlike naphthalene, which lacks polar functional groups, benzil possesses two ben-zene rings and two polar functional groups, leading to a synergistic effect between the above-mentioned interactions [15,29]. Similarly, 1.2-dichlorobenzene has only one benzene ring in its chemical structure, which can explain its inferior performance in comparison to benzil.…”
Section: Selection Of Sorbent and Its Amountmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that benzil outperformed the others (Figure 2A), which could be attributed to some interactions, such as π-π, hydrophobic, and semi-H-bond interactions between benzil and the targeted analytes. Unlike naphthalene, which lacks polar functional groups, benzil possesses two ben-zene rings and two polar functional groups, leading to a synergistic effect between the above-mentioned interactions [15,29]. Similarly, 1.2-dichlorobenzene has only one benzene ring in its chemical structure, which can explain its inferior performance in comparison to benzil.…”
Section: Selection Of Sorbent and Its Amountmentioning
confidence: 99%
“…This is especially the case, when chromatographic techniques are coupled with a mass spectrometry detector without prior sample preparation/extraction [12,13]. Additionally, since TFs predominantly are present in trace levels in real samples, a preconcentration step is typically necessary [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the sorbent is eluted with an appropriate organic solvent and the resulting eluent is utilized in the following extraction or determination step [14]. This method was used for the extraction of various pesticides from different foodstuffs [15][16][17]. Although DSPE is an efficient and facile approach obtaining high enrichment factors (EFs) is not accessible in this method because of using a high volume of elution solvent.…”
Section: Introductionmentioning
confidence: 99%